A Gender-Based Maqashid Sharia Study of Penghulu in Indonesia (A Study of Jasser Auda's Views) - Maliki, Ibnu Akbar; Zaelani, Abdul Qodir; Ardi, Muh Zaitun; Ghummiah, Shivi Mala (Nurani, 2023)
The Penghulu in Indonesia has always been identified and held by men instead of women. The legal opportunity in Ministry of Religious Affairs Regulation No. 20/2019 on Marriage Registration has been annulled by Compilation of Islamic Law (KHI), which requires men as guardians, where the existence of marriage guardians is one of the duties of the head of the family, which inhibits women from serving as head of the family. Although fiqh as the main source of KHI has given legality to women as marriage guardians, KHI does not adopt arguments in favour of women becoming marriage guardians. Whereas the duties of the penghulu are not only limited to wali hakim, there are many duties of benefit in marriage such as providing legal certainty through marriage registration. This article aims to find out the existence of female headmen in Indonesia in the perspective of maqashid sharia. The research employs a literature content analysis. The results showed that based on the study of the six features of maqashid sharia proposed by Jasser Auda, the existence of female headmen is basically something that should be commonplace in Indonesia. The value of maslahah behind the administrative duties and legal certainty of marriage is an objective reason for women to serve as penghulu. This is because realising benefit is the obligation and responsibility of every human being, regardless of gender. This is supported by the existence of cognitive features, wholeness, openness, interrelationship between levels, multi-dimensionality, and meaningfulness of women's headship which has fulfilled the elements of maslahat and the objectives of Islamic law. Therefore, through this research, the reconstruction of guardianship law in KHI should be carried out immediately so that it can pave the way for women to access the position of penghulu.